Turkish Midwifery Students’ Fear of Delivery Process - BAYRI BİNGÖL, FADİME (My University, 2019)
Introduction: Fear affects a person's decision-making process and causes a midwife to make a wrong decision about normal vaginal delivery and cesarean delivery, so research was carried out in order to determine the fields related to delivering process in which students experience the most fear and feel sufficient. Methods: A descriptive/cross-sectional study was performed between September and October 2017. The sample consisted of 732 students selected with the convenience maximum variation sampling method from six universities studying in the third and fourth years of a midwifery program. The study measured data collected with a questionnaire entitled "Midwives' Fear of Delivery Process". The data were analyzed in with the SPSS for Windows using percentage and mean values and Spearman correlation test. Results: In general, students are more afraid of practices with which they say they have more experience such as vaginal palpation (3.30 (0.884), rs=0.131, P<0.001), and they are less afraid of practices (interventional) with which they have less experience such as breech delivery (1.70 (0.915), rs=0.048, P=0.197) or no experience at all and of cases in which they can get hurt. The students feel most sufficient when performing prenatal and postnatal practices. Conclusion: The results of our study parallel the conclusion in the literature that students are afraid of the fields that they have practiced most. Before clinical practice, instructors can determine students' fears and deficiencies in relation to procedures and areas of practice and can develop approaches for alleviating their fears and weaknesses.
Keywords: Fear; Students; Midwifery; Delivery; Labor